2022
DOI: 10.3389/fphys.2022.994454
|View full text |Cite
|
Sign up to set email alerts
|

Facial mask acute effects on affective/psychological and exercise performance responses during exercise: A meta-analytical review

Abstract: Background: Face masks are widely used during the COVID-19 pandemic as one of the protective measures against the viral infection risk. Some evidence suggests that face mask prolonged use can be uncomfortable, and discomfort can be exacerbated during exercise. However, the acute responses of mask-wearing during exercise on affective/psychological and exercise performance responses is still a topic of debate.Purpose: To perform a systematic review with meta-analysis of the acute effects of mask-wearing during e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
2
2
0
Order By: Relevance
“…The increase in Dys when wearing a mask in our study is consistent with a 2022 meta-analysis that found a moderate effect of surgical masks on subjective Dys with physical exertion (22). A recent review proposed several potential mechanisms for this effect, including possible CO 2 rebreathing with mask use, as well as influences related to changes in temperature and/or moisture of the face and mask (23).…”
Section: Discussionsupporting
confidence: 92%
“…The increase in Dys when wearing a mask in our study is consistent with a 2022 meta-analysis that found a moderate effect of surgical masks on subjective Dys with physical exertion (22). A recent review proposed several potential mechanisms for this effect, including possible CO 2 rebreathing with mask use, as well as influences related to changes in temperature and/or moisture of the face and mask (23).…”
Section: Discussionsupporting
confidence: 92%
“…This study provides several future research questions that could not be clarified within its scope. Based on recent reviews [9][10][11][12] and our results, the physiological effect of mask wearing is probably insignificant or small for short-term walking. However, the multitask gait was found to have an effect on the correct answer rate of the calculation task, as well as on the gait pattern, in the present study; however, varying results have been reported.…”
Section: Discussionsupporting
confidence: 60%
“…However, adverse effects of wearing face masks have been reported, including perceived breathlessness or dyspnea 1) , thermal changing (i.e., increase in skin temperature under the mask or exertion and heat perception) [2][3][4] , headaches 5,6) , skin reactions (i.e., acne, itches) 7) . Dyspnea or breathlessness is most likely caused by increased breathing resistance 1,8,9) , reinspiration of CO2 in exhaled air built up in the mask 9) , and an increase in the dead space, depending on mask type 8,10) . Therefore, although masks are worn for a variety of purposes, various adverse effects have also been observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation